Penta and hexanuclear nickel tiara-like clusters with two different thiolate bridges1. Issue 27 (21st July 2015) - Tan, Chunhong; Jin, Meiliang; Zhang, Hao; Hu, Shengmin; Sheng, Tianlu; Wu, Xintao
<x xml:space="preserve">Abstract</x> The infrequent pentanuclear tiara and hexanuclear tiaras with two different types of mono and bidentate thiolates were obtained. These heretofore unknown additions to the cyclo-[Ni(μ-SR)2]n tiara family are of particular interest, which are often constructed by just one kind of thiolate ligand.